The Age-Related Changes in Speed of Visual Perception, Visual Verbal and Visuomotor Performance, and Nonverbal Intelligence During Early School Years - Alghamdi, Rana J.; Murphy, Melanie J.; Goharpey, Nahal; Crewther, Sheila G. (Frontiers in Human Neuroscience, 2021)
Speed of sensory information processing has long been recognized as an important characteristic of global intelligence, though few studies have concurrently investigated the contribution of different types of information processing to nonverbal IQ in children nor looked at whether chronological age or months of early schooling played a larger role. Thus, this study investigated speed of visual information processing in three tasks including a simple visual inspection time (IT) task, a visual-verbal processing task using Rapid Automatic Naming (RAN) of objects as an accepted preschool predictor of reading, and a visuo-motor processing task using a game-like iPad application, (the ‘SLURP’ task) that requires writing like skills, in association with nonverbal IQ (Raven’s Coloured Progressive Matrices) in children (n=100) aged 5 to 7 years old. Our results indicate that the rate and accuracy of information processing for all three tasks develops with age, but that only RAN and SLURP rates show significant improvement with years of schooling. RAN and SLURP also correlated significantly with nonverbal IQ scores, but not with IT. Regression analyses demonstrate that months of formal schooling provide additional contributions to speed of dual task visual-verbal (RAN) and visuomotor performance and Raven’s scores supporting the domain-specific hypothesis of processing speed development for specific skills as they contribute to global measures such as nonverbal IQ. Finally, RAN and SLURP are likely to be useful measures for early identification of young children with lower intelligence and potential poor reading.